Evidence for boron incorporation into the serpentine crystal structure - Pabst, Sonja; Zack, Thomas; Savov, Ivan P.; Ludwig, Thomas; Rost, Detlef; Vicenzi, Edward P. (American mineralogist, 2011)
Serpentinite mud volcanoes from the Mariana forearc comprise B-rich mantle wedge peridotites serpentinized by slab fluids. The major component of these rocks are serpentine group minerals [Mg 3 Si 2 O 5 (OH) 4 ], showing highly variable textural and geochemical features. Micro-Raman spectroscopy reveals that the serpentine minerals are well-crystallized lizardite and chrysotile. In situ SIMS spot analyses and element mapping via ToF-SIMS show that B is evenly distributed across serpentine grains, suggesting that serpentine, both lizardite and chrysotile in different textural regions, can host significant amounts of B (up to -200 μg/g) into its crystal structure. As such structurally bound B can only be released during recrystallization or serpentine breakdown, our results have implications for modeling of the efficiency of cross-arc fluid mobile element recycling in subduction zones and stress the importance of the hydrated forearc mantle as a reservoir for fluid mobile elements.